Ethnic Specificity of Cultural Codes - Vladimir M. Savitskij (Publishing house "Sreda", 2020)
The author compares and analyzes some definitions of the concept of cultural code offered by Russian and foreign linguists and semiologists. Aspects of this concept are singled out and described. Regulatory, semiotic and retransmitting functions of cultural codes are briefly characterized. The relationship between the concepts of cultural code and picture of the world is revealed. The author's interpretation of the concept of cultural code is given, the ethnic specificity of cultural codes is revealed, its factors are described, participation of cultural codes in forming ethnic mentality is demonstrated. The author shows discrepancies in understanding reality due to the difference in the cultural codes used and points out that the role of cultural code can be performed by any perceptible area of reality: landscapes, natural phenomena, fauna, flora, artifacts (household utensils, tools, weapons, garments of clothes, dwelling places etc.) and actions with the listed items. All this is regarded in the article as semiotic means of thinking and communication. Methods. The analysis of cultural codes was carried out by using the methods of cross-cultural analysis and interlingual comparison on the material of English and Russian metaphoric set phrases. Conclusion. The conclusion is made concerning the influence of cultural codes on the choice of the path of historic development and, ultimately, on the fates of nations.